The Difficult Items Analysis in Listening Test at Senior High School 1 Tambang - Gushendra, Rizky; Ramadoni, Iqbal (State Islamic University of Sultan Syarif Kasim Riau, 2017)
This study aims to determine the level of difficulty in the question items given to students in the Listening test. The Listening Test here is on the Listening Section of the English National Examination in two academic years, 2015/2016 and 2016/2017, focusing solely on investigating the difficult items and represented components of the declared items Listening Section in the National Exam of English in the academic year 2015/2016 and 2016/2017 on twelfth-grade students in SMA Negeri 1 Tambang. In this descriptive quantitative study, the writer took thirty students as a sample of 203 students to obtain difficult items of students in the Listening Section in the English National Examination. They are consisted of fifteen items for each academic year. The results of data analysis show that there are some items that are difficult for students. For Listening Section in English National Examination 2015/2016, there are three items that are declared difficult. the items are item 3, item 9 and item 11. And for Listening Section in English National Examination 2016/2017 shows six items that are declared difficult. They are item 2, item 8, item 9, item 11, item 13, item 15. Therefore, the Listening Section component in the English National Examination of 2015/2016 which is also difficult to do is component 1, component 3, and component 4. Moreover, the Listening Section in the English National Examination in 2016/2017 which is also difficult to do is component 1, component 3, component 4 and component 5.